Assessment of Allelic Distribution and Multiplicity of Infection in the Three Northern Local Government Area, Taraba State, Nigeria - Chibuzor Obiorah Sylvester; Allahnanan Emmanuel; Peace Christopher Njideka; Chukwuebuka Igboaka Duke (Darul Yasin Al Sys, 2025)
All the three allele types for MSP1- K1, MAD20 and RO33 and of MSP2- 3D7 and FC27 were identified in Zing and Lau, except in Jalingo where RO33 of the MSP1 family was not amplified. In Jalingo, mono-infection was observed in K1 with the highest frequency of 28 (25%) and MAD20 3 (2.7%). RO33 mono-infection was not seen. Mixed infection was seen in K1+MAD20, 13 (11.6%), K1+RO33, 12 (10.7%) and K1+MAD20+RO33, 15 (13.4%). In Zing, unlike Jalingo K1 has the lowest allele frequency 3 (2.6%) for mono-infections, MAD20 23 (19.8%) and RO33 26 (22.4%) with the highest frequency. Mixed infections include K1+MAD20 4 (3.4%), K1+RO33 1 (0.9%), MAD20+RO33 11 (9.5%) and K1+MAD20+RO33 17 (14.7%). In Lau, 10 (9.2%) alleles were found for K1, 20 (18.3%) for MAD20 and 4 (3.7%) RO33 mono-infections. Mixed infections include 32 (29.4%) K1+MAD20 with highest frequency, 2 (1.8%) k1+RO33, 4 (3.7%) MAD20+RO33 and 2 (1.8%) K1+MAD20+RO33. For the MSP2 family, 24 (21.4%) 3D7, 11 (9.8%) FC27 and 33 (29.5%) mixed infection of 3D7+FC27 in Jalingo. In Zing, 28 (24.1%) 3D7, 15 (12.9%) FC27 and 42 (36.2%) mixed infection of 3D7+FC27. Also, in Lau, 30 (27.5%) 3D7, 12 (11.0%) FC27 and 38 (34.9%) mixed infection of 3D7+FC27. The allelic diversity of P. falciparum MSP1 and MSP2 is mostly due to meiotic recombination events involving genetically distinct parasite clones that infect the same mosquito vector, and hence, human host. Therefore, the proportion of mixed infections and the number of clones per individual is one of the prerequisites to generate new genotypes and to increase the diversity of the parasitic population. Multiple clonal infections with different genotypes of P. falciparum were identified among the P. falciparum isolates in the study locations with a moderately high Multiplicity of Infection (MOI). Haematological and biochemical tools are recommended as an adjunct tool in the management of malaria infection especially in underdeveloped countries like Nigeria.